2020
DOI: 10.9779/pauefd.592287
|View full text |Cite
|
Sign up to set email alerts
|

Kavram Karikatürlerinin Fen Eğitimi Dersi Akademik Başarısı Üzerindeki Etkisini Belirlemeye Yönelik Bir Meta-Analiz Çalışması

Abstract: Bu araştırmanın amacı, Türkiye'de 2007-2019 yılları arasında kavram karikatürlerinin Fen Eğitimi dersi akademik başarısı üzerindeki etkisini inceleyen deneysel çalışmaların meta-analizini yaparak genel etki büyüklüğünü hesaplamak ve bu etkinin çeşitli moderatörlere göre anlamlı farklılık gösterip göstermediğini belirlemektir. Araştırma kapsamında birbirinden bağımsız deneysel çalışmaların sonuçlarını birleştirmek için meta-analiz yöntemi kullanılmıştır. Elde edilen çalışmalardan deneysel veya yarı deneysel yön… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…According to the results obtained from the study, it was stated that the cooperative learning approach had a positive and strong effect on student's academic achievement. Yokuş and Ayçiçek (2019) conducted a meta-analysis study to determine the effect of concept cartoons on science course academic achievement. Based on the findings of this study, it was stated that the learning-teaching processes in which concept cartoons were at the center were effective on students' academic achievement, and the average effect size value obtained from the studies was positive and had a significant effect size.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results obtained from the study, it was stated that the cooperative learning approach had a positive and strong effect on student's academic achievement. Yokuş and Ayçiçek (2019) conducted a meta-analysis study to determine the effect of concept cartoons on science course academic achievement. Based on the findings of this study, it was stated that the learning-teaching processes in which concept cartoons were at the center were effective on students' academic achievement, and the average effect size value obtained from the studies was positive and had a significant effect size.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Numerous studies in the literature indicate that these methods increase students' achievement (Ayaz & Söylemez,2015;Chen & Yang, 2019;Donker et al, 2014;Ileri et al, 2020;Lei et al, 2022;Orhan, 2019;Orhan & Durak Men, 2018;Ören, 2020;Yokuş & Ayçiçek, 2019). In this respect, a study evaluating the approaches used in a constructivist learning environment was conducted by Ayaz and Şekerci (2015).…”
Section: Introductionmentioning
confidence: 99%
“…When the related literature was examined, a meta-analysis study based on CKCM was not found. However, in the literature, there are studies investigating the effects of different teaching methods and techniques on academic achievement according to the duration of the experimental procedure (Yokuş and Ayçiçek, 2020;Kaldırım and Tavşanlı, 2018;Çapar and Tarım, 2015;Bahadırhan, 2019). Suggestions are given in the light of the findings of the research.…”
Section: Discussionmentioning
confidence: 99%
“…Sentezleme aşamasında farklı etki büyüklükleri kullanılan meta-analiz modeli büyük önem taşımaktadır. Heterojenlik testi, dâhil edilme kriterleri doğrultusunda ulaşılan çalışmaların niteliği üzerinde durarak kullanılacak modelin karar verilmesine yardımcı olmaktadır (Yokuş & Ayçiçek, 2019). Meta-analiz için iki popüler istatistiksel model bulunmaktadır, bunlar sabit etkiler modeli ve rastgele etkiler modelidir (Borenstein vd., 2010).…”
Section: Verilerin Analiziunclassified